IrisNet: An Architecture for a Worldwide Sensor Web - Gibbons, Phillip B.; Karp, Brad; Ke, Yan; Nath, Suman; Seshan, Srinivasan (IEEE Pervasive Computing, 2003)
Today’s common computing hardware—Internet connected desktop PCs and inexpensive, commodity off-the-shelf sensors such as Webcams—is an ideal platform for a worldwide sensor web. IrisNet provides a software infrastructure for this platform that lets users query globally distributed collections of high-bit-rate sensors powerfully and efficiently.